2022
DOI: 10.1016/j.omtn.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of individual FDA-approved clinical drugs identifies modulators of nonsense-mediated mRNA decay

Abstract: Nonsense-mediated mRNA decay (NMD) degrades transcripts with premature stop codons. Given the prevalence of nonsense single nucleotide polymorphisms (SNPs) in the general population, it is urgent to catalog the effects of clinically approved drugs on NMD activity: any interference could alter the expression of nonsense SNPs, inadvertently inducing adverse effects. This risk is higher for patients with disease-causing nonsense mutations or an illness linked to dysregulated nonsense transcripts. On the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…Nonsense-mediated mRNA decay is a critical cellular surveillance mechanism, the enrichment of which underscores potential genetic contributions to AV stenosis and represents a novel avenue for repurposing therapeutic nonsense-mediated mRNA decay inhibition. 34 Electron microscopy has shown calcified EVs to be present in mineralized regions of both tissues, 8,14 consistent with the substantial enrichment of vesicle ontologies shared by the disease-altered proteomes of carotid arteries and AVs.…”
Section: Discussionmentioning
confidence: 79%
“…Nonsense-mediated mRNA decay is a critical cellular surveillance mechanism, the enrichment of which underscores potential genetic contributions to AV stenosis and represents a novel avenue for repurposing therapeutic nonsense-mediated mRNA decay inhibition. 34 Electron microscopy has shown calcified EVs to be present in mineralized regions of both tissues, 8,14 consistent with the substantial enrichment of vesicle ontologies shared by the disease-altered proteomes of carotid arteries and AVs.…”
Section: Discussionmentioning
confidence: 79%
“…In mammalian cells, alternative splicing coupled to nonsense-mediated decay (i.e., AS-NMD) is a conserved post-transcriptional regulation mechanism in which alternative splicing can alter the reading frame to produce a PTC-containing transcript subject to NMD [24,[55][56][57][58][59].…”
Section: Colocalization Of S Colocalization Of S Colocalization Of Smentioning
confidence: 99%
“…Our own analysis of the GENCODE annotation showed that about 12% of natural transcripts are presumably targeted by NMD regulation, since they follow the 50-nt rule (i.e., the presence of a terminal codon >50 nt upstream of the last exon-exon junction). Accordingly, NMD factors are implicated in cellular homeostasis, stress response, cell cycle, differentiation, development, neural activity, immunity, and spermatogenesis [15][16][17][18][19][20][21][22][23][24]. NMD typically downregulates its substrate by 2-20 folds [25,26], generating significant functional and clinical implications.…”
mentioning
confidence: 99%
“…Cardiac glycosides target Na-K ATPase on the cell membrane to increase intracellular Ca2 + levels and inhibit NMD [ 101 ]. Through profiling multiple endogenous NMD targets, Zhao et al identified several NMD modulators, including the anticancer drug homoharringtonine [ 102 ]. Given the diversity of methods that can be used to suppress NMD, NMD inhibition holds a promising therapeutic potential for ameliorating a variety of disease phenotypes.…”
Section: Targeting the Ejc And Nmd In Diseasesmentioning
confidence: 99%